Highway to Cocytus or Ascent into Paradise: Apatheia and Moral Bioenhancement - Parks, Benjamin N. (Christian bioethics, 2022)
With the godlike powers of modern technology, just one bad actor can unleash hell on Earth. In the face of this threat posed by technology, some have proposed moral bioenhancement as a solution. Although moral bioenhancement may at first seem like something Christian should support, it is my contention in this paper that there is at least one significant reason for Christians to be cautious in their appropriation of moral bioenhancement technology: it can at best give us a false apatheia, which runs the ironic risk of destroying our ability to make moral progress.